Penyelesaian Sengketa Perasuransian oleh Badan Mediasi dan Arbitrase Asuransi Indonesia (BMAI) - Ida Ayu Surya Dwijayanti; I Nyoman Puru Budiartha; Desak Gde Dwi Arini (Warmadewa Press, 2021)
Disputes are common in the business world. The insurance industry is no exception. The Indonesian Insurance Mediation and Arbitration Agency is a legal entity in. the form of an association that is independent and impartial, June/ions to resolve dispute claims (claims for compensation or benefits) between the Insurer (Insurance Company) and the Insured (Policy Holder). In this research raises two problem formulations, first What is the function of BMAI in the settlement of insurance disputes and second is How is the Settlement of Insurance Disputes by BMAI. The type of research is the type of Normative Law research. The approach method used is the statutory approach. Meanwhile, the technique of collecting legal materials is the technique of reading and understanding as well as searching using the internet, the research result states that BMAI functions as a settlement institution for Insurance Disputes between the Insured and the Insurer that occurs in Indonesia. BMAI Will accept all complaints of Insurance Claim disputes submitted by the insured party and the insurer and the proposed dispute must meet the settlement requirements by BMAI. The Settlement of Insurance Check by BMAI is completed in three stages, namely, Mediation, Adjudication, and the Arbitration